Perbankan Umum Syariah Jangka Panjang Dan Pendek Terhadap Pertumbuhan Ekonomi Di Indonesia (Error Correction Model) - Wahyudi, Heru; Astuti, Nova Diah (Penerbit Goodwood, 2022)
Purpose: This study aims to analyze the influence of Islamic banking which is reflected in: assets, financing, and third party funds of Islamic banking on economic growth in Indonesia. The data used in this study is time series data in the form of quarter period 2011:Q1-2020:Q4. Research methodology: This study uses regression analysis methods OLS (Ordinary Least Square) and ECM (Error Correction Model). The data used is time series data in the form of quarterly period 2011:Q1-2020:Q4. Results: The results of this study indicate that the asset variable in Islamic banking has a positive and significant effect on economic growth in Indonesia in the short and long term. The financing variable in Islamic banking has a positive and significant effect on economic growth in Indonesia in the short and long term. Likewise, the DPK (Third Party Funds) variable for Islamic banking has a positive and significant impact on economic growth in Indonesia, both in the short term and in the long term.Limitations: The limitation of this research is that there are many variables outside the model that are not included in the study. Contribution: The positive performance of the financial sector will have a positive correlation with the economic performance of a country. The financial sector can be the main source of growth in the real sector of the economy.